PEMODELAN NUMERIK SEBARAN OKSIGEN TERLARUT DI ESTUARI WONOREJO, SURABAYA DAN DAMPAKNYA TERHADAP EKOSISTEM ESTUARI - Wazirotus Sakinah; Saifurridzal Saifurridzal; Alaudin Alaudin (Journal of Aceh Aquatic Sciences, 2021)
Wonorejo river estuary is a wide estuary in Surabaya. It becomes mangrove conservation area. But, many land conversion from mangroves to ponds up to the dense pollution on the river neighbour make water quality issues especially for DO in that water. Based on this situation, the aim of this study is to find distribution of DO in Wonorejo river estuary, to know that water quality standard based on the quality standard criteria, and to know the effect of DO Wonorejo river estuary into estuarine ecosystem. A hydrodynamic and water quality model with MIKE 21 Hydrodynamics and ECO Lab module are used to examine distribution of water quality parameters in Wonorejo river estuary in one month at dry season. Validation used DO measurement in 10 sites along Wonorejo estuary at same season. Then, analyze the impact into estuarine ecosystem was used. DO concentration has interval 5,26 - 5,72 mg/L at high tide and 5,027 - 5,65 mg/L at low tide. After one month, DO in estuary has the highest concentration 5,536 mg/L. Based on literature, this concentrations can make shrimps growth bothered. But, this concentration is still not exceeding from quality standard for marine biota in Environment Ministry Regulation Number 51/2004. Optimizing the role of Local Government and mangrove rehabilitation according to procedures in the estuary area.